Using Music to Decolonize the Teaching of Comprehensive Sexuality Education in Zambian Schools: A Content Analysis Study - Muzata, Kenneth (Papanda Publisher, 2025)
This paper addresses an important issue regarding the introduction of Comprehensive sexuality education in the Zambian school curriculum and questioning whether such an introduction entailed the lack of comprehensive sexuality education content in the Zambian culture or not. Using selected pieces of music content, the Paper analyses how CSE is covered within the Zambian cultural curriculum and implores school authorities to tap from indigenous knowledge to feed the curriculum rather than bowing to foreign content. This paper adopted a qualitative approach. Five purposively selected songs from four artists and five grade five and six learners’ books were subjected to content analysis to determine the adequacy of CSE content. The learners’ books were used to examine the availability of CSE content in the school system. Findings revealed that, although the selected songs did not address specific grade levels to benefit from CSE content, there was available content which when integrated in the Zambian school curriculum would adequately teach comprehensive sexuality education content and skills to learners in schools. Future CSE curriculum reviews should consider utilizing the Zambian music in the teaching of CSE in schools.